PERLINDUNGAN HUKUM TERHADAP JUSTICE COLLABORATOR TERKAIT PENANGANAN TINDAK PIDANA KORUPSI DI INDONESIA - Rika Ekayanti (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
The discussion in this thesis raised regarding Legal Protection against Justice Collaborator in the handling of corruption in Indonesia. The objectives of this study are to be analyzed with both forms of regulation and identify the type of protection provided by the laws of the State of Indonesia justice collaborator and determine the accuracy of the strength of the evidential value of the testimony in the trial of a justice collaborator, by analyzing the legal provisions in the legislation other law relating to witnesses. This type of research is used in a scientific journal this is the kind of normative legal research, because there is disharmony norm based research in the form of a legal vacuum regarding the setting justice collaborator in formal laws and regulations in Indonesia, as well as the legal ambiguities in the text of the legislation on Article 10 paragraph (2) Law No.. 13 of 2006 on the Protection of Witnesses and Victims of the justice collaborator testimony that can be used as consideration to give the judge for leniency. Having regard to the development of the current law that requires courage and willingness of law enforcement in combating corruption as an extraordinary crime, it is necessary to break the law through the use of an instrument justice collaborator.